1996
DOI: 10.1136/ard.55.6.370
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of anal function in patients with systemic sclerosis.

Abstract: Objective-To investigate anorectal function in women patients with systemic sclerosis (SSc), with and without lower gastrointestinal symptoms. Methods-Anorectal manometry was performed in 16 patients with SSc: six with no or minimal bowel symptoms, seven with constipation, and three with diarrhoea and faecal incontinence. Eleven healthy women acted as control subjects. Pressure data were recorded via an eight lumen polyvinylchloride water perfused catheter. Station and rapid pull through techniques were used.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2003
2003
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 18 publications
0
6
0
Order By: Relevance
“…This result strongly supports the idea that poor function of the smooth internal anal sphincter muscle causes faecal incontinence in SSc. Others have shown a reduced anal resting pressure in SSc patients (12)(13)(14)(24)(25)(26), and by means of ultrasonography, some authors have found either fibrosis and thinning (12) or oedema and thickening (27) of the internal anal sphincter.…”
Section: Discussionmentioning
confidence: 98%
“…This result strongly supports the idea that poor function of the smooth internal anal sphincter muscle causes faecal incontinence in SSc. Others have shown a reduced anal resting pressure in SSc patients (12)(13)(14)(24)(25)(26), and by means of ultrasonography, some authors have found either fibrosis and thinning (12) or oedema and thickening (27) of the internal anal sphincter.…”
Section: Discussionmentioning
confidence: 98%
“…The resting pressure of the anal sphincter was reported to be normal 174, 185 or decreased 164, 184, 186 . A decrease was noted in the maximum squeeze pressure of the anal sphincter, 186 the rectal capacity and rectal wall compliance 164, 169, 183, 184, 187, 188 . The rectoanal inhibitory reflex (RAIR) was reported to be normal in a few studies 164, 174 but diminished or absent in the majority of studies 162, 183, 185, 186, 188–192 .…”
Section: Anorectummentioning
confidence: 99%
“…Fibrotic degeneration of the IAS causes faecal incontinence in 38% of SSc patients [6]. This process is reflected by reduced anal resting pressure [7][8][9][10][11][12][13][14] and thinning of the IAS when evaluated by endoanal ultrasonography [11,15]. The effects of SSc and fibrosis of the IAS on anal biomechanics remain obscure.…”
Section: Introductionmentioning
confidence: 99%